Data Mining: Competitive Tool to Digital Library - Lone, Tariq Ahmad; Khan, Rafi Ahmad (DESIDOC Journal of Library & Information Technology, 2014)
The increasing popularity of world wide web is providing an easy and quick alternative to get the required information through the internet which has threatened the existence of traditional libraries. The human capital associated with the management of libraries in the contemporary world is facing the challenge of crafting strategies to continuously augment their services with the help of information technology to provide quality customised services to the end users. To address this challenge libraries can use data mining to extract strategic information from the data captured in the libraries’ data ases. The capability of data mining to solve some of the vital problems has encouraged libraries to implement this intelligent tool of data mining. In this paper, an attempt has been made to educate stakeholders on the issues and applications of data mining in libraries. http://dx.doi.org/10.14429/djlit.34.6722